THE LAWSUIT OF THE TWO ALLOWANCES TEAMS AND THEIR TREATMENTS ACCORDING TO THE MODERN TRENDS OF THE COURTS OF APPEAL IN THEIR DISCRIMINATORY CAPACITY - Dr. Yousif Sami Yousif (Scholars Digest Publishing, 2024)
This article examines the complexities surrounding the legal treatment of property sale contracts in Iraq, particularly focusing on the lawsuit regarding the difference between two property valuations. It highlights key findings, including the critical role of formalities in real estate transactions and the lack of a clear definition of property ownership transfer in the Iraqi Civil Code. The analysis reveals significant amendments to compensation guidelines through Revolutionary Command Council Decree No. 1198, aimed at aligning with economic realities and promoting justice. The study notes discrepancies in court decisions, particularly regarding the need for written contracts, the application of penalty clauses, and the procedural capacity for lawsuits involving deceased sellers. Furthermore, it addresses the limitations imposed by the Iraqi legislator on buyers seeking recovery of property prices and related compensation. The article concludes with recommendations for legislative reforms to standardize judicial practices, revise outdated legal texts, and extend protections to encompass all real estate rights.
Keywords: Lawsuit, Two Allowances Teams, Modern Trends of The Courts of Appeal and Discriminatory Capacity.